2020
DOI: 10.3390/su12020675
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Consumers’ Preferences for Bio-Based Apparel: A German Case Study with a Functional Rain Jacket Made of Bioplastic

Abstract: Plastic pollution is an increasing global problem, however, replacing fossil resources with bioplastics made from renewable resources could be part of the solution. Currently, no research analyzing the influencing factors for consumers’ preferences for functional apparel made of bioplastic material could be found. To close this gap in research, we conducted this study with a sample of 1673 participants that were representative of the German population aged 16 years and above. We conducted a choice based conjoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 72 publications
6
37
0
Order By: Relevance
“…In addition, Scherer et al (2017) noted that ecologically sensitive consumers are more innovative than consumers of conventional plastic. Klein et al (2020) showed that more innovative consumers are more in favor of biobased products. Therefore, an individual's interest in innovation seems to have a positive impact on their decision to purchase eco-friendly apparel.…”
Section: Innovativenessmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, Scherer et al (2017) noted that ecologically sensitive consumers are more innovative than consumers of conventional plastic. Klein et al (2020) showed that more innovative consumers are more in favor of biobased products. Therefore, an individual's interest in innovation seems to have a positive impact on their decision to purchase eco-friendly apparel.…”
Section: Innovativenessmentioning
confidence: 99%
“…Blesin et al (2017) showed that past product experience leads to a greater purchase intention for bio-based products. Additionally, Klein et al (2019Klein et al ( , 2020 showed that previous product experiences increase the probability of purchasing bio-based products. Therefore, previous consumer behavior is expected to affect consumers' acceptance of moderate prices for bio-based apparel.…”
Section: Attitude Toward Bioplasticsmentioning
confidence: 99%
See 3 more Smart Citations